Assessment of the availability of strategic planning for human resources in the Syrian Telecom Company in Sweida (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to assess the availability of strategic planning for human resources in the Syrian Telecom Company in Sweida, by addressing four basic dimensions (business analysis - demand forecasting - supply analysis - gap analysis). The researcher relied on the comprehensive inventory method for the study community, by distributing (180) questionnaires to the employees at the studied company, which were fully retrieved and analyzed. The researcher used T Student test for one sample as a basic test for this study to evaluate the availability of the dimensions of strategic planning for human resources.   The research found a high level of both business analysis and demand forecasting on the one hand, and a low level of both supply analysis and gap analysis on the other hand. The research also concluded with a set of recommendations related to the necessity of creating an integrated system for strategic planning for human resources, and balancing the demand and supply of human resources, with the establishment of specialized training courses to raise the efficiency of employees in human resources management.